Agricultural socialized services and Chinese food security: examining the threshold effect of land tenure change - Cai, Baozhong; Wangda, Liao; Shi, Fang; Abate, Meseret Chanie; Geremew, Betelhemabraham; Addis, Amsalu K. (Frontiers in Sustainable Food Systems, 2024)
Revolutionary agricultural structural reforms in the supply chain and cutting-edge institutional mechanisms are pivotal in catalyzing a quantum leap in food production. China's focus on achieving self-sufficiency in grain production for domestic security necessitates structural reforms in the agricultural supply chain and innovative institutional mechanisms. The emergence of socialized agricultural institutions plays a pivotal role in providing essential services to smallholder farmers. However, a dearth of studies evaluating the efficacy of these services in enhancing grain production exists. This study aims to fill this gap by analyzing provincial panel data from China spanning 2011 to 2020 to evaluate the impact of Agricultural Socialized Services (ASS) development levels on grain production. Employing panel and panel threshold models for empirical analysis, the research investigates how this impact varies between major grain-producing regions and non-major grain-producing regions. Findings indicate a significant positive effect of ASS on grain production, with a correlation coefficient of 1.3555. While its impact is less pronounced in grain-producing regions, it proves beneficial in non-grain regions. Moreover, the transfer of farmland use rights amplifies ASS's influence on grain production, with a threshold value of 33.18%. The study concludes by outlining policy implications from various perspectives, providing practical recommendations for policymakers and stakeholders in the agricultural sector.